A ubiquitous tire rubber–derived chemical induces acute mortality in coho salmon - Tian, Zhenyu; Zhao, Haoqi; Peter, Katherine T.; Gonzalez, Melissa; Wetzel, Jill; Wu, Christopher; Hu, Ximin; Prat, Jasmine; Mudrock, Emma; Hettinger, Rachel; Cortina, Allan E.; Biswas, Rajshree Ghosh; et al. (Science (American Association for the Advancement of Science), 2021)
For coho salmon in the U.S. Pacific Northwest, returning to spawn in urban and suburban streams can be deadly. Regular acute mortality events are tied, in particular, to stormwater runoff, but the identity of the causative toxicant(s) has not been known. Starting from leachate from new and aged tire tread wear particles, Tian et al. followed toxic fractions through chromatography steps, eventually isolating a single molecule that could induce acute toxicity at threshold concentrations of ∼1 microgram per liter. The compound, called 6PPD-quinone, is an oxidation product of an additive intended to prevent damage to tire rubber from ozone. Measurements from road runoff and immediate receiving waters show concentrations of 6PPD-quinone high enough to account for the acute toxicity events. Science , this issue p. 185 A toxic transformation product of a tire rubber antioxidant explains mortality in salmon exposed to urban stormwater. In U.S. Pacific Northwest coho salmon ( Oncorhynchus kisutch ), stormwater exposure annually causes unexplained acute mortality when adult salmon migrate to urban creeks to reproduce. By investigating this phenomenon, we identified a highly toxic quinone transformation product of N -(1,3-dimethylbutyl)- N ′-phenyl-p-phenylenediamine (6PPD), a globally ubiquitous tire rubber antioxidant. Retrospective analysis of representative roadway runoff and stormwater-affected creeks of the U.S. West Coast indicated widespread occurrence of 6PPD-quinone (<0.3 to 19 micrograms per liter) at toxic concentrations (median lethal concentration of 0.8 ± 0.16 micrograms per liter). These results reveal unanticipated risks of 6PPD antioxidants to an aquatic species and imply toxicological relevance for dissipated tire rubber residues.